Infection complications after transrectal ultrasound-guided prostate biopsy: A radiology department’s experience and strategy for improvement - Brassil, Michael; Li, Yangmei; Ordon, Michael; Colak, Errol; Vlachou, Paraskevi (Canadian Urological Association Journal, 2022)
Introduction: Transrectal ultrasound (TRUS)-guided prostate biopsy is a common procedure performed to diagnose prostate cancer. The risk of infection complications is well-described in the literature, and strategies to avoid such complications continue to evolve over time. We performed a retrospective review of our infection complications and propose a strategy for improvement. Methods: We reviewed clinical outcomes from patients undergoing TRUS-guided prostate biopsy at our institution from November 2018 to November 2020. We reported the antimicrobial prophylaxis received, whether the biopsy was systematic or targeted, and we examined the rate of clinically significant infection complications and hospitalization. Results: Among 312 men who underwent TRUS-guided prostate biopsy during the study period, seven (2.2%) had an infection. Four patient groups with distinct antimicrobial regimen were identified; the largest of these patient groups received a three-day course of cefixime and a single dose of fosfomycin (59%). The proportion of patients with infection complications across these groups did not demonstrate a statistically significant difference (p=0.803). There was no significant difference in proportion of infection between systematic and targeted biopsy groups (3.0% vs. 0%, p=0.204). The proportion of patients hospitalized was 1.3%, with a mean length of stay of four days. Conclusions: We report a rate of clinically significant infection following TRUS-guided prostate biopsy of 2.2%. Due to our referral pathway, we have an inconsistent approach to antimicrobial prophylaxis, although there was no statistically significant difference in infection rate between the groups. We propose a standardized approach that may lead to improved patient outcomes.